ASSESSMENT OF DURABILITY AND CHARACTERISTICS OF CHANGES IN KEFIR MADE FROM COW'S AND GOAT'S MILK - SARICA, E.; COŞKUN, H. (Italian Journal of Food Science, 2020)
Present study was aimed to determine the changes and the best consumption time of kefir samples made from cow and goat milk using starter culture during the storage at the refrigerator (+4°C for 35 days). It was found that goat kefir (GK) samples had higher pH and lipolysis values during storage while cow kefir (CK) samples had higher values of viscosity. The counts of lactococci, lactobacilli, leuconostoc, total mesophilic aerobic bacteria, acetic acid bacteria and yeast decreased during the storage. Amounts of lactic, acetic, citric, pyruvic and oxalic acids were higher in GK samples. Acetaldehyde, diacetyl and acetoin contents were higher in CK samples. The highest sensory scores were obtained for CK samples on 14th day and for GC sample on 21th day of the storage.